When the Minimum Wage Really Bites Hard: Impact on Top Earners and Skill Supply - Terry Gregory; Ulrich Zierahn (Institute of Labor Economics (IZA), 2020)
We investigate minimum wage spillovers by exploiting the first-time introduction of a minimum wage within a quasi-experiment in a context with an extraordinary large bite: the German roofing industry. We find positive wage spillovers for medium-skilled workers with wages just above the minimum wage, but negative effects for high-skilled top earners in East Germany, where the bite was particularly pronounced. There, the minimum wage lowered both returns to skills and skill supply. We propose a theoretical model according to which negative spillovers occur whenever a negative scale effect dominates a positive substitution effect and provide empirical support for our theory.
Keywords: J31; J38; J24; C21; J23; 330; minimum wages; wage effects; spillover effects; wage restraints; returns to skills; unconditional quantile regression; scale effect; substitution effect; skill supply